Effects of Selective Genetic Introgression from Wild Soybean to Soybean. Issue 6 (1st November 2014) - Akpertey, Abraham; Belaffif, Mohammad; Graef, George L.; Rouf Mian, M. A.; Grover Shannon, J.; Cregan, Perry B.; Hudson, Matthew E.; Diers, Brian W.; Nelson, Randall L.
ABSTRACT: Soybean [ Glycine max (L.) Merr.] breeding in the United States currently relies on a narrow genetic base. For decades, but more intensely in recent years, efforts have been made to incorporate exotic soybean germplasm into the breeding pool. Although wild soybean ( G. soja Seib. and Zucc.) is genetically much more diverse than soybean, much less effort has been devoted to utilizing wild soybean in soybean breeding. The objectives of this research were to identify high‐yielding lines derived from crosses between five wild soybean accessions and soybean cultivars and determine if there are differences in the genetic contributions of each wild soybean parent. Each wild soybean was crossed to Williams 82, and the F1 plants were backcrossed to Williams 82 to create the backcross generation (BC1 ) lines. The BC2 parent lines were developed through family selection and backcrossed to Williams 82, IA2052, IA3023, or LN97–15076. Family selection beginning in the F2 generation was used to develop lines from plant introduction (PI) 507807 and PI 549046. The lines from PI 479767 and PI 483461 were selected by early generation testing through yield testing F2 lines in the F3 and F4 generations. The lines derived from PI 65549 were developed from a single seed descent (SSD) population. Field evaluation of the derived lines identified lines that are not significantly different from their recurrent parents. Using single nucleotide polymorphism (SNP) markers, we found unique contributions being made by the G. soja parents. Despite intense selection pressure to recover good agronomic types, an average of 13% of SNP alleles in the derived lines came from the G. soja parents.